Evaluating Prior Pap Screening Intervals Among Women With Newly Diagnosed Cervical Cancer. (21st September 2018) - Bonafede, Machaon; Miller, Jeffrey; Pohlman, Scott; Vilalta, Adrian; Troeger, Kathleen; Felix, Juan
Abstract: Objectives: To describe the prevalence of cervical cancer screening prior to diagnosis of cervical cancer and evaluate the screening interval against established guidelines. Methods: Women aged 21 to 64 years with a new diagnosis of cervical cancer between 2010 and 2016 were identified in the IBM MarketScan Explorys Claims-EMR Data Set, which includes detailed administrative medical and pharmacy claims data and clinical and laboratory information commonly found in electronic medical records. The incidence of cervical cancer was defined using ICD-9/10 codes. Pap tests that occurred within 12 months of the diagnosis were considered part of the diagnostic event. The interval between prior Pap testing and the cancer diagnosis was evaluated. Results: In total, 2, 624 women (mean age = 48.8 years) with newly diagnosed cervical cancer were included in the analysis. Prior to their cancer diagnosis, approximately one-half (46%) of women were enrolled in a commercial insurance program for an average of 3.6 years; the look-back period ranged between 2.5 and 6 years, during which 74% of women had evidence of prior Pap screening, while 26% did not have a record of a prior Pap test, although 83.5% of these women had at least one physician visit in the year prior to their cervical cancer diagnosis. Among women with a prior Pap test, the average interval between the Pap exam and cancer diagnosis was 2.5 years. Conclusions: The majority of women with newly diagnosed cervical cancer had evidence of screening events that occurred within the recommended 3-year screening interval. This challenges the conventional belief that most cases of cervical cancer occur in unscreened or underscreened women. The observation that most unscreened women had concurrent medical encounters underscores the role of health care providers to reinforce the importance of routine cervical cancer screening to improve the opportunity for earlier detection and prevention of cervical cancer.